(untitled) (Global Journal of Human-Social Science, 2024)
Facebook fulfils many functions Users engage with this platform for a myriad of reasons and these are well documented and researched In white informal settlements in Gauteng South Africa residents are using Facebook for survival In this qualitative study participants in two white informal settlements share how they connect with donors sponsors through Facebook and how their active Facebook marketing campaigns secure a steady stream of donations This intersects the link between social capital and poverty and it challenges the notion that the poor universally lacks bridging social capital loose social ties with people in higher socio-economic brackets Through in-depth semistructured interviews participants explain how they use Facebook to increase their bridging social capital and to leverage their networks for the purpose of getting by